THE EXISTENCE OF CHINESE ETHNIC IN THE TOWN OF BLANG PIDIE ACEH BARAT DAYA REGENCY - Rahmad Sepia Fikri Abdullah; Nasruddin AS; Reza Idria (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
The existence of Chinese ethnic in the southwest coast of Aceh is estimated to have arrived before Indonesian independence and even currently they still live in the town of Blang Pidie, Aceh Barat Daya Regency. The purpose of this study is to examine the existence of Chinese ethnic in the Town of Blang Pidie, their growth, cultures, and relations with the surrounding communities. This is a qualitative research by combining library and field study. The data collection techniques used were observation, interview and documentation. The analysis of the data was conducted through data reduction, data presentation and conclusion. The results showed that the existence of Chinese ethnic in the Town of Blang Pidie had a major influence in the trade sector at both the regional and national levels, contributing to the competition among local traders, being in collaboration with agencies of Aceh Selatan government, especially in goods for office purposes. Their development is in the field of education by sending their children to public schools from elementary to higher education in Aceh and abroad. From the trade sector, they are involving in building a molding factory, wood factory, rice milling factory, beverage company transportation services and others. Chinese ethnic culture preserves the culture of its ancestors, both in celebrating the Chinese New Year, marriage customs, and maintaining religious values ​​that are considered sacred. Meanwhile, the interaction with the community is positive as they are active in participating in activities such as gotong royong, sports, wedding parties, death ceremonies and helping people experiencing disasters by providing groceries.